Trial and evaluation of intelligent road studs for hazard warning - Crawford, C.B; Doran, V.P.A (12th IEE International Conference on Road Transport Information & Control - RTIC 2004, 2004)
During the summer of 2002, the Scottish Executive commissioned FaberMaunsell to advance their technical and operational understanding of intelligent road studs (IRS) and evaluate the potential for trial implementation on the Scottish trunk road network. To define the applications potential in Scotland, FaberMaunsell undertook a number of studies investigating available technologies, associated functionalities and operational requirements. Based on these study's findings, the Scottish Executive is installing a trial IRS system on the M8 motorway approaching Glasgow. Upon completion, this trial system will be capable of providing enhanced lane delineation, traffic monitoring, fog detection, automatic incident detection and hazard warning functionalities. The paper gives an overview of the progress made during these studies, subsequent installation works and trial, identifying the potential wider use of IRS for hazard warning.